Efeito da densidade de semeadura na produção do amendoim - Nakagawa, J.; Lasca, D. D.; Neves, JPD; Neves, G. D.; Sanches, S. V.; BARBOSA, V; Dasilva, M. N.; Rossetto, CAV (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
In this work, the effects of sowing densities on peanut (Arachis hypogaea L.) crop, cv. Tatu were studied. Three experiments were carried out under field conditions on a soil classified as ''Latosol Roxo'', in the Municipality of Pontal, SP, during the wet seasons of 1987-88, 1988-89, and 1989-90. The densities studied were 7, 10, 13, 16, 19, 22, 25, and 28 seeds in one metter of row, under some row spacing of 0.60 m. The pod number per plant was the yield component responsible for the variation of pod production per plant and these decreased with the increase of sowing density. However. The low pod production per plant in high densities of sowing was compensated by the high populations of plants and these produced high yield. Thus, good pod yields were obtained, without significant losses of yield compared with the higher densities, at density of 13 seeds per meter, in 1987-88, 16 seeds per meter in 1988-89 and 10 seeds per meter in 1989-90, that resulted, respectively, in 11.36, 12.72 and 9.28 plants per meter at harvest time.

Para estudar, na cultura do amendoim, o efeito da densidade de semeadura sobre a produção de vagens e seus componentes, foram realizados três experimentos, em condições de campo, em um Latossolo Roxo, no município de Pontal, SP, com a cultivar Tatu, nos anos agrícolas de 1987/88, 1988/89 e 1989/90, em cultivo das águas. As densidades estudadas foram 7, 10, 13, 16, 19, 22, 25 e 28 sementes por metro linear, em espaçamento comum de 0,60 m entrelinhas. O número de vagens por planta, nos três experimentos, foi o componente de produção responsável pela variação da produção de vagens por planta, tendo diminuído com o aumento da densidade de semeadura. A menor produção/planta nas densidades maiores de semeadura foi, todavia, compensada pela maior população de plantas, originando, nestas, maiores produções de vagens (kg/ha). Assim, produções de vagens (kg/ha), sem perdas significativas em relação às densidades maiores, foram obtidas nas densidades de 13 sementes/m em 87/88, de 16 sementes/m em 88/89, e de 10 sementes/m em 89/90, que originaram, respectivamente, 11,36, 12,72 e 9,28 plantas/m à colheita.
Effects of sowing densities on peanut production
Keywords: ARACHIS HYPOGAEA L; POD YIELD; AND YIELD COMPONENTS